AWCL: Adaptive weighted centroid target localization algorithm based on RSSI in WSN - Yanjun Chen; Quan Pan; Yan Liang; Zhentao Hu (2010 3rd IEEE International Conference on Computer Science and Information Technology, 2010)
Target localization and tracking is the canonical application of Wireless Sensor Networks. Unlike a centralized system, a sensor network is subject to a unique set of resource constraints such as limited on-board battery power and limited network communication bandwidth. So the traditional tracking algorithm can be directly used in WSN. Therefore efficient localization algorithms that consume less energy for computation and less bandwidth for communication are needed. The weighted centroid localization algorithm (WCL) based on RSSI is applied in most of actual systems. Only one uniform path loss exponent obtained through experiments is used to calculate the weights of nodes in general WCL. It is well known that the path loss exponent is the essential reflection of sensing surroundings. The actual sensing scenario can't be revealed in the traditional WCL algorithm, and therefore it is not appropriate that only one exponent is accepted all through the area covered by the sensor nodes. A new algorithm, adaptively weighted centroid localization (AWCL), is proposed in this paper. Firstly a more reasonable path loss exponent is adaptively estimated according to the surroundings where the target nodes situates. Secondly the target position will be calculated by using the weighted centroid method in which exponents estimated in the first stage are adopted. Theoretical analysis are presented to demonstrate the performance of the proposed localization method, the simulation results show that that the proposed algorithm outperforms the general WCL algorithm.